The inter relevance of literature and psychology: exploring the psychological characters in the Indian English novels - Kruti J. Desai (AG Volumes, 2022)
Literature, a subject that combines history, philosophy, sociology, psychology, and so on, it is a discipline that uses language as a medium of expression to comprehend human life, culture, and the world around us. The purpose of this study is to explore literature in the area of its interdisciplinary structure, psychology in particular, taking into consideration man and existence, personality, and individual differences, all of which have been investigated throughout history by authors, philosophers, artists, psychologists, and psychiatrists, among others. Fictional characters have long been connected with a wide range of enigmatic concepts, enigmatic personalities, and enigmatic reasons. For example, Madame Bovary is used to explain the word Bovarism. In literary works, there are several instances of this. Literature has explored human nature and the nature of life long before psychology was ever a field of study. The primary facts in the discipline of psychology may be found in works of literature and art that help people become more self-aware and curious about their own unique selves and the world around them. A significant connection between literature and psychology can be clearly noticed since the two disciplines deal with the same subject matter: the human psyche and how it reacts to and responds to various situations.